A curse for true love ebook - Garber, Stephanie (Once Upon a Broken Heart, 2023)
Blood will be shed, hearts will be stolen, and true love will be put to the test in A CURSE FOR TRUE LOVE , the breathtaking conclusion to Stephanie Garber's #1 NEW YORK TIMES bestselling Once Upon A Broken Heart trilogy Two villains, one girl, and a deadly battle for happily ever after. Evangeline Fox ventured to the Magnificent North in search of her happy ending, and it seems as if she has it. She's married to a handsome prince and lives in a legendary castle. But Evangeline has no idea of the devastating price she's paid for this fairytale. She doesn't know what she has lost, and her husband is determined to make sure she never finds out. . . . but first he must kill Jacks, the Prince of Hearts. Also by Stephanie Garber: The Caraval Series - Caraval - Legendary - Finale